Composition Of Shark Species In Fishing Centers Catch Air Rami Beach Air Rami District Of Mukomuko Regency - Wido Ariesma (Unversitas Muhammadiyah Mataram, 2022)
Abstract: This study aims to determine the composition of shark species caught by fishermen at the Air Rami Coastal Capture Fisheries Center, Air Rami District, Mukomuko Regency. The method used in this study is a descriptive method that describes or describes the nature of a phenomenon or situation that exists at the actual time and examines the causes of certain symptoms as well as data analysis of fishing gear and operating techniques derived from android-based questionnaires (KoBoCollect), tabulated in tabular form and analyzed descriptively. During the study, there were 4 types of sharks, namely Sphyrna lewini, Carcharhinus sorrah, Loxodon macrorhinus, Paragaleus tengi with 56 fish species. The most dominant shark caught was Sphyrna lewini, which was 42 (75%). All types of shark caught in the Air Rami Coastal Capture Fisheries Center, Air Rami District, Mukomuko Regency, are species included in the IUCN list and the Sphyrna lewini shark is listed in the CITES Appendix under the category of Appendix II.Abstrak: Penelitian ini bertujuan untuk mengetahui komposisi jenis ikan hiu yang tertangkap oleh nelayan di Sentra Perikanan Tangkap Pantai Air Rami Kecamatan Air Rami Kabupaten Mukomuko. Metode yang digunakan pada penelitian ini adalah metode deskriptif yang menggambarkan atau menguraikan sifat dari suatu fenomena atau keadaan yang ada pada waktu aktual dan mengkaji penyebab dari gejala-gejala tertentu serta analisis data alat tangkap dan teknik operasi penangkapan berasal dari kuisioner berbasis android (KoBoCollect), ditabulasikan dalam bentuk tabel dan dianalisis secara deskriptif. Komposisi jenis ikan hiu di Sentra Perikanan Tangkap Pantai Air Rami Kecamatan Air Rami Kabupaten Mukomuko selama penelitian terdapat 4 jenis ikan hiu yaitu Sphyrna lewini, Carcharhinus sorrah, Loxodon macrorhinus, Paragaleus tengi dengan jumlag total ikan hiu yang tertangkap adalah 56 ekor. Hiu yang paling dominan tertangkap adalah jenis Sphyrna lewini yaitu sebanyak 42 ekor (75%). Semua jenis ikan hiu tersebut yang tertangkap di Sentra Perikanan Tangkap Pantai Air Rami Kecamatan Air Rami Kabupaten Mukomuko adalah spesies yang termasuk dalam daftar list IUCN dan hiu Sphyrna lewini terdaftar dalam Appendik CITES dengan kategori Appendik II.